Antena Mikrostrip Rectangular Patch 1575,42 MHz dengan Polarisasi Circular untuk Receiver GPS - Teguh Firmansyah; Sabdo Purnomo; Feti Fatonah; Tri Hendarto Fajar Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
In this paper, a rectangular-shaped microstrip patch antenna at frequency 1575.42 MHz for GPS receiver applications is designed, fabricated, and evaluated. In order to produce circular polarization, dual-feed method is proposed. The dimensions of this antenna are: substrate length (Wg) 91 mm; substrate width (Lg) 90 mm; patch length (W) 62,5 mm; patch pidth (L) 47 mm; feed channel 50 Ω (w) 3,01 mm; and feed channel 100 Ω (w') 0,63 mm. The simulation result shows that at center frequency 1575,42 MHz, return loss has a value of -24.44 dB and VSWR 1,12. It was also obtained bandwidth 59 MHz with a frequency range from 1520 MHz to 1620 MHz. The antenna has a gain 3.514 dBi. The measurement results obtained VSWR 1,094 and return loss -26,998 dB. The center frequency was shift to 1574.52 MHz with VSWR 1,067 and return loss -29,566 dB. Additionally these antennas also have value in the -15 dB bandwidth of 9.3 MHz with axial ratio less than -3 dB. The axial ratio less than -3dB shows that this antenna has circular polarization.